PROSES PENCIPTAAN KOMPOSISI MUSIK “DEK RANG MI” - Auzy Madona Adoma (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The democracy in Minangkabau society is always guided by the expression of duduak surang basampik-sampik, duduak basamo samo balapang lapang, duduak samo randah tagak samo tinggi. From the philosophy below the reseacher express it into the creation of musical composition entitled “Dek Rang Mi” taken from a fragment of Rang Minangkabau Democracy. This music creation was provided three interpretation. First, it was interpreted the meaning of duduak surang basampik sampik, means the process of how we can appreciate people’s opinion. The second interpretation was about the meaning of duduak basamo balapang lapang which is democratic life in society, also it was interpreting individual importance that merge into the important of group communities. The third interpretation the meaning of duduak samo randah tagak samo tinggi means in the deliberation can reveal their opinions freely without any exception. Keywords : Democracy, philosophy, meaning, creation.